Discrimination and Disidentification: The Fair-Start Defense of Affirmative Action - Himma, K. E. (Journal of business ethics, 2001)
The Fair-Start Defense justifies affirmative action preferences as a response to harms caused by race- and sex-based discrimination. Rather than base a justification for preferences on the traditional appeal to self-esteem, I argue they are justified in virtue of the effects institutional discrimination has on the goals and aspirations of its victims. In particular, I argue that institutional discrimination puts women and blacks at an unfair competitive disadvantage by causing academic disidentification. Affirmative action is justified as a means of negating this unfair disadvantage.